Commissioning personalised care in the English adult social care sector: an action research model to support leadership development. Issue 1 (4th February 2014) - McCray, Janet; Palmer, Adam
Abstract : Purpose: – The purpose of this paper is to present the perspectives of English adult social care sector partners on the qualifications and standards required for leaders as they prepare to meet the demands of commissioning personalised care. Continuing an action research cycle guided by Coghlan and Brannicks (2010, p. 4) organisational centred model (McCray and Palmer, 2009) it benefits from the previous experience and reflection in action of the partners and researchers. Set in a general social care context, lessons learned from the study outcomes will be of interest to both commissioners of services and service users with acquired brain injury. Design/methodology/approach: – A model of action research informed by Coghlan and Brannicks' (2010, p. 4) organisational centred model focused on context, quality of relationships, quality of the research process and its' outcomes was used. The role of the authors was to facilitate diagnosis of the leadership issues arising from the implementation of personalised care in the English adult social care sector and in collaboration with sector partners seek resolutions. Six focus groups comprising two commissioners, service providers, user group and care manager/social work leads were facilitated at two separate events in the south of England. Findings: – Findings presented are derived from focus group discussions with strategic and organisational leaders and service user partners from the English adult social care sectors. Analysis of focus group data identified a number of themes. The overarching themes of human resource management, gaps in industry standards and leadership are discussed here. Whilst industry sector standard qualifications and frameworks may be at the centre of strategic planning for transformation, findings here have identified that additional support will be required to create leaders who can commission successfully to create cultural change. New approaches to leadership development may be needed to facilitate this process. Research limitations/implications: – The study offers a single method qualitative research approach based on two local authorities in the south of England. It presents a localised and particular view of leadership development needs. Practical implications: – The paper shows how action research can make a contribution to knowledge and practice. Originality/value: – The paper provides interesting new insights into the skills for commissioning in a changing public and third sector environment with reference to commissioning personalised support for people with brain injury.